Urbanization alters plastic responses in the common dandelion Taraxacum officinale. Issue 9 (27th March 2020) - Pisman, Matti; Bonte, Dries; de la Peña, Eduardo
Abstract: Urban environments expose species to contrasting selection pressures relative to rural areas due to altered microclimatic conditions, habitat fragmentation, and changes in species interactions. To improve our understanding on how urbanization impacts selection through biotic interactions, we assessed differences in plant defense and tolerance, dispersal, and flowering phenology of a common plant species ( Taraxacum officinale ) along an urbanization gradient and their reaction norms in response to a biotic stressor (i.e., herbivory). We raised plants from 45 lines collected along an urbanization gradient under common garden conditions and assessed the impact of herbivory on plant growth (i.e., aboveground biomass), dispersal capacity (i.e., seed morphology), and plant phenology (i.e., early seed production) by exposing half of our plants to two events of herbivory (i.e., grazing by locusts). Independent from their genetic background, all plants consistently increased their resistance to herbivores by which the second exposure to locusts resulted in lower levels of damage suffered. Herbivory had consistent effects on seed pappus length, with seeds showing a longer pappus (and, hence, increased dispersal capacities) regardless of urbanization level. Aboveground plant biomass was neither affected by urbanization nor herbivore presence. In contrast to consistent responses in plant defenses and pappus length, plant fitness did vary between lines. Urban lines had a reduced early seed production following herbivory while rural and suburban lines did not show any plastic response. Our results show that herbivory affects plant phenotypes but more importantly that differences in herbivory reaction norms exist between urban and rural populations. Abstract : We assessed differences in plant traits in a common plant species ( Taraxacum officinale ) originating from different lines along an urbanization gradient and their reaction norms in response to a biotic stressor (i.e., herbivory) under common garden conditions. We found that differences in herbivory reaction norms exist between urban and rural populations, but they seem to be trait‐dependent.